2008
DOI: 10.1007/s11745-008-3176-3
|View full text |Cite
|
Sign up to set email alerts
|

N‐3 Polyunsaturated Fatty Acids Modulate In‐Vitro T Cell Function in Type I Diabetic Patients

Abstract: In this work, we assessed the in-vitro effects of eicosapentaenoic acid (EPA; C20:5n-3) and docosahexaenoic acid (DHA; C22:6n-3) (final concentration, 15 microM) on T cell blastogenesis, interleukin-2 and -4 (IL-2, IL-4) secretion, fatty acid composition and intracellular oxidative status in type I diabetic patients with or without complications. Con A stimulated lymphocyte proliferation, glucose uptake, intracellular reduced glutathione levels and catalase activity were lower in diabetics as compared to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 47 publications
4
34
0
Order By: Relevance
“…This interaction requires high concentrations of AA, and any change in this may affect TCR-MHC complex affinity and TCR signal transduction, determining the nature and magnitude of the T-cell response. There are in vitro studies showing the regulatory effect of AA metabolites on the development and function of immune system cells including growth and differentiation of thymocytes, proliferation and migration of T-cells, Th1 and Th2 response mediated by cytokines, antigen presentation, macrophage regulation, TNF α , IL-1 and IL-2 production, as well as suppressor T-cell induction [3, 53, 5557]. …”
Section: Fatty Acidsmentioning
confidence: 99%
“…This interaction requires high concentrations of AA, and any change in this may affect TCR-MHC complex affinity and TCR signal transduction, determining the nature and magnitude of the T-cell response. There are in vitro studies showing the regulatory effect of AA metabolites on the development and function of immune system cells including growth and differentiation of thymocytes, proliferation and migration of T-cells, Th1 and Th2 response mediated by cytokines, antigen presentation, macrophage regulation, TNF α , IL-1 and IL-2 production, as well as suppressor T-cell induction [3, 53, 5557]. …”
Section: Fatty Acidsmentioning
confidence: 99%
“…Oxidative stress was found to influence the proliferation, activation, cytokine secretion and T‐cell homeostasis . Enhanced intracellular free radical production or reduced antioxidant enzyme activity have been shown to induce T lymphocyte oxidative stress …”
Section: Introductionmentioning
confidence: 99%
“…Modulation of immune system by consumption of vegetable oils protected against some diseases. N‐3 polyunsaturated fatty acids (PUFA) improved T cell intracellular oxidative status in diabetes . An important source of dietary n‐3 PUFA is α ‐linolenic acid (ALA, C18:3 n‐3), supplied by vegetable sources such as linseed oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORAC has been found to be a good index of oxidative stress in diabetes mellitus (Merzouk et al, 2004). Our data revealed that the total antioxidant activity (ORAC) decreased in the plasma of children with diabetes in favor of an oxidative stress in such patients.…”
Section: Discussionmentioning
confidence: 55%